Dominasi dan Perkembangan Musik Keroncong dalam Ibadah Kaum Muda-Mudi Gereja Injili di Tanah Jawa di Era Disrupsi - Simatupang, Jhonnedy Kolang Nauli; Aritonang, Jhon Wesley Boiman Parasian; Lumban Tungkup, Hizkia (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
The purpose of this study is to understand how keroncong music is dominant in times of change in the musical world, how keroncong music is currently developing, and how they can help the youth of the Evangelical Church of Java were to find out how it is evident in the worship of the Lord. Research methods were used in writing the work. This scientific method is library research. This was carried out by the author. That is a search for articles, books, and encyclopedias on topics related to the dominance and development of Keroncong music. Javanese Evangelical Church Youth Worship in Turbulent Times. The findings of this study are as follows: First, in the middle of the inevitable turbulent times, the dominance of Keroncong music begins to weaken, especially among the youth. There is Java worships evangelical church people, so care must be taken to adapt to existing changes Java evangelicalism continues to evolve with new faces and appearances. Simply as a form of following the development of existing music and maintaining keroncong music in the youth liturgy. Third, the church must embrace existing changes without losing the identity and culture that has existed in the church for many years. But without an openness to existing change, especially during turbulent times, the church will fall behind over time.